Manoeuvring and positioning of an intelligent sub-sea vehicle - Lau, Michael. (2008)
The significant achievements of the project are as follows: a. Development of an integrated Trainer, Simulator and Operation Console. It incorporates a Virtual Environment. The pilot can select either a training or pre-flight planning mode. b. Modelling and control of the ROV. The URV uses a combination of four actuators for 6 Degree of Freedoms movements in which not all can be controlled independently. The main achievement is the development of a method in the controller design that fully exploits the dynamic model structure of the ROV. This enables the ROV I to be operated in a manual cruise ('fly') and station keeping ('positioning') modes. Significant modification in the hardware has also been done to facilitate the improved control and operations of the ROV. c. The development of a Navigation System for the ROV. The work of RG 74/98 has resulted in understanding of the functions of various types of sensors, their effective range and the design of the best parameters for their operation. There is now a platform for study into data fusion and data mining, which will lead towards the goal of achieving autonomous vehicle system.